Desain Sistem Informasi Akuntansi Keuangan Masjid - Nugraha, Farhani Kautsar; Wahyuni, Endang Dwi; Anwar, Achmad Syaiful Hidayat (Universitas Muhammadiyah Yogyakarta, Indonesia, 2014)
The purpose of this research is to describe and redesign accounting information system of cash receipts and cash expenditure in Masjid Agung Jami’ Kota Malang. This research is case study with analysis description method. Designing the accounting information system in order to increase control effectiveness of cash receipt and cash expenditure. The result of analysis, describe that in few transaction in Masjid Agung Jami’ there are double function, not complete of receipt, and financial reporting using cash basic. Then researcher designing with other function involvement also additional cashier function, additional few document, and using Microsoft Excel with accrual basic accounting.